2015
DOI: 10.1186/s12889-015-2427-5
|View full text |Cite
|
Sign up to set email alerts
|

When children play, they feel better: organized activity participation and health in adolescents

Abstract: BackgroundParticipation in organized leisure-time activities (OLTA) has been linked to healthy youth development. This study aimed to assess whether participation in OLTA is associated with both physical and mental health in adolescents, and whether this association differs by pattern of activity participation, age and gender.MethodsThe present study was based on data from the 2013/2014 Health Behaviour in School-aged Children study in the Czech Republic. This data concerned 10,503 adolescents (49.2 % boys) ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 48 publications
11
89
0
3
Order By: Relevance
“…In contrast, Denault et al (2009) observed the intensity of participation in art activities to be predictive of lower alcohol consumption, and Sharp et al (2015) found that children taking part in multiple activities reported significantly lower levels of substance use. This is in line with our findings and only underpins the assumption that the actual type (pattern in our case) of activity matters (Badura et al 2015). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Denault et al (2009) observed the intensity of participation in art activities to be predictive of lower alcohol consumption, and Sharp et al (2015) found that children taking part in multiple activities reported significantly lower levels of substance use. This is in line with our findings and only underpins the assumption that the actual type (pattern in our case) of activity matters (Badura et al 2015). …”
Section: Discussionsupporting
confidence: 93%
“…First, the OLTA participation was investigated using a dichotomous variable (participation in at least one OLTA vs. in no OLTA ). Next, the respondents were split into five groups of OLTA participation patterns (Table 1) based on a cluster analysis (Badura et al 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structured leisure-time activities might contribute to higher levels of intrinsic motivation and positive youth development 8 and are associated with better physical and mental health among adolescents. 9 In contrast to other Western countries, like the United States and UK, organized sports in northern Europe and the Nordic countries in particular is strongly related to time after school, and there has been little or no collaboration between school and sports clubs. 10 It is estimated that 88% in Finland 11 and 70%-80% of all children in Norway 12 at some point during their childhood or adolescence are members of a sports club or team.…”
Section: Mathisen Et Almentioning
confidence: 99%
“…In a modern lifestyle, time after school has an important potential for physical activity in the lives of children and adolescents. Structured leisure‐time activities might contribute to higher levels of intrinsic motivation and positive youth development and are associated with better physical and mental health among adolescents . In contrast to other Western countries, like the United States and UK, organized sports in northern Europe and the Nordic countries in particular is strongly related to time after school, and there has been little or no collaboration between school and sports clubs .…”
Section: Introductionmentioning
confidence: 99%